Primary Rosai-Dorfman disease in the maxilla; a case report and literature reviewPrimary Rosai-Dorfman disease in the maxilla; a case report and literature review - Vergara Gárate, Valentina (2020)
Rosai-Dorfman is a rare benign disease of unknown etiology, recognized as sinus histiocytosis with massive lymphadenopathy. It mainly affects children and young adults of African descent and although its treatment is not clear, the prognosis is usually favorable. We present a rare and unusual clinical manifestation of a unilateral right maxillary tumor in a 59-year-old woman diagnosed with Rosai-Dorfman disease after a rigorous clinical, imaging, and histological study. The treatment with systemic corticosteroids and radiotherapy for this unusual clinical manifestation turned out to be successful in this case, however, more studies are required to verify its effectiveness.